2017
DOI: 10.1158/1078-0432.ccr-16-2439
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Trial Characteristics and Barriers to Participant Accrual: The MD Anderson Cancer Center Experience over 30 years, a Historical Foundation for Trial Improvement

Abstract: Purpose Slow-accruing clinical trials delay the translation of basic biomedical research, contribute to increasing healthcare costs, and may prohibit trials from reaching their original goals. Experimental Design We analyzed a prospectively maintained institutional database that tracks all clinical studies at the MD Anderson Cancer Center. Inclusion criteria were: activated phase I-III trials, maximum projected accrual ≥10 participants, and activation prior to March 25, 2011. The primary outcome was slow acc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
33
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 28 publications
1
33
0
Order By: Relevance
“…Even when investigators enroll an adequate number of participants, they rarely do so on schedule [4, 7], or in a manner that attracts the full range of eligible participants [8, 9]. Further, participant recruitment represents one of the largest costs of conducting clinical trials, requiring an average of 13 hours and $500 per subject in cancer trials at academic medical centers [10].…”
Section: Introductionmentioning
confidence: 99%
“…Even when investigators enroll an adequate number of participants, they rarely do so on schedule [4, 7], or in a manner that attracts the full range of eligible participants [8, 9]. Further, participant recruitment represents one of the largest costs of conducting clinical trials, requiring an average of 13 hours and $500 per subject in cancer trials at academic medical centers [10].…”
Section: Introductionmentioning
confidence: 99%
“…Due to this patient recruitment dilemma, a number of analyses have assessed the impact of individual clinical trial characteristics on patient recruitment in an effort to understand how best to structure and design new studies (9)(10)(11). Tang et al focused on oncology trials at MD Anderson Cancer Center and found that sponsor type, longer time to first enrollment, and high target accrual were associated with slow recruitment rate (12). For clarity, the official National Cancer Institute definition for trial sponsor is "a person, company, institution, group, or organization that oversees or pays for a clinical trial and collects and analyzes the data" (13).…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5] Even at National Cancer Institutedesignated comprehensive cancer centers with large referral populations, approximately 20% to 40% of interventional trials accrue slowly (defined as the enrollment of fewer than 2 participants per year). 3,6 Barriers to clinical trial enrollment are a topic of active investigation because these obstacles are of concern to oncologists, policy makers, advocacy groups, trial sponsors, and professional societies, as well as to the general population, who call for more rapid progress in therapy for cancer. 3,6 Barriers to clinical trial enrollment are a topic of active investigation because these obstacles are of concern to oncologists, policy makers, advocacy groups, trial sponsors, and professional societies, as well as to the general population, who call for more rapid progress in therapy for cancer.…”
Section: Introductionmentioning
confidence: 99%
“…1 As a result, approximately 20% of publicly funded prospective clinical trials fail due to a lack of accrual, and oncology has the lowest likelihood of drug approval from phase 1 among 14 major disease areas, despite public interest in access to novel agents as exemplified by "Right To Try" legislative proposals. [2][3][4][5] Even at National Cancer Institutedesignated comprehensive cancer centers with large referral populations, approximately 20% to 40% of interventional trials accrue slowly (defined as the enrollment of fewer than 2 participants per year). 3,6 Slow accrual may worsen as trials increasingly enroll small, molecularly defined patient subgroups.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation